Analisis Kesulitan Siswa dalam Belajar Materi IPA dan Upaya Penyelesaiannya Melalui Pendekatan Eksperimen - Najma Fatikha Nasroellah; Muhammad Suwignyo Prayogo; Ananda Julia Afiva; Sinta Nur Salsa Billa (Jurnal Pustaka Cendekia Pendidikan, 2025)
This study aims to identify the difficulties faced by students in learning science subjects in elementary school and to find solutions through experimental learning methods. Many students find it difficult to understand science concepts, which are often abstract and difficult to relate to everyday life. To overcome this, experimental learning is carried out by providing direct experience through experiments, so that students can more easily understand and feel the concepts being learned. The results of the study show that the experimental method can increase student interest and engagement as well as their learning outcomes. However, the success of this method is also influenced by the readiness of teachers and the availability of adequate practical tools. Therefore, it is necessary to develop an experimental model that suits the needs and characteristics of students so that the learning process becomes more effective and enjoyable. This research is expected to serve as a reference in improving the quality of science learning in elementary schools so that students not only memorize but truly understand and are skilled in science.